Pengaruh Biaya Promosi dan Pendapatan Bersih Terhadap Nilai Perusahaan Makanan dan Minuman Tahun 2015-2019 - Muthia Berliana; Gusganda Suria Manda (Journal of Business and Economics Research (JBE), 2021)
This study aims to determine the effect of promotion costs and net income on firm value either partially or simultaneously. In this study using quantitative data sourced from the financial statements of the food and beverage sub-sector manufacturing companies on the IDX in 2015-2019, based on the purposive sampling method 8 companies were sampled from 24 populations. The results showed that: promotion costs partially have an influence on firm value, while net income partially has no effect on firm value, in simultaneous research promotion costs and net income have an influence on firm value.